Marketing Malaysia to the Middle East Tourists: towards a preferred inter-regional destinations - Ahmad Azmi M. Ariffin; Mohd Safar Hasim (Institut Kajian Rantau Asia Barat, 2009)
This paper attempts to demonstrate the importance of the Middle East market to the Malaysian tourism industry, to discuss their travel profiles and behavior, and finally to suggest strategies to better position Malaysia as the most preferred inter-regional destination among the Arab tourists. It is estimated that there will be a total of 35 million outbound tourist arrivals from the Middle East in 2020. The Arab tourists tend to stay longer, spend more and are unfazed by the high tropical temperatures. The Middle East region is also a very viable market for tourism as it is home to a growing young population with a high per capita income, particularly the Saudi Arabia and UAE. This paper also discusses the pattern of outbound tourism from the region as well as the marketing efforts undertaken by the Malaysian tourism players to attract the Middle East travelers. Malaysia promotional efforts so far very much concentrated for tourism products and services within the Klang Valley area and tourism players in other parts of the country are still far from the so called “Arab Tourist’s Friendly”. It is suggested that Malaysia should focus more of their marketing efforts to well capture the Saudi Arabia and UAE outbound travel, to develop distinctive youth-oriented tourism products, to increase air links between major tourist cities in Malaysia and the Middle East, to start fully utilize the internet media for promotion and distribution, and to encourage the Arabs to purchase timeshare vacation homes in Malaysia.